Acute Effects of Ethanol on Hippocampal Spatial Representation and Offline Reactivation - Miyake, Kosaku; Yagi, Saichiro; Aoki, Yuki; Shikano, Yu; Ikegaya, Yuji; Sasaki, Takuya (Frontiers in Cellular Neuroscience, 2020)
Acute alcohol exposure impairs hippocampus-dependent spatial memory. However, there is little evidence for the effects of ethanol on the spike patterns of hippocampal cell populations. Here, we examined how the spatial firing patterns of place cells, neurons that encode specific locations, were altered in rats that were intraperitoneally injected with 1.5 g/kg ethanol. Ethanol administration partly reduced or abolished place-selective spiking of a subset of place cells during running periods in a spatial task, whereas a subset of place fields newly emerged, suggesting partial reorganization of hippocampal spatial maps by ethanol. On the other hand, ethanol administration did not significantly alter the frequency of hippocampal sharp wave ripples and synchronous spike patterns during resting periods, suggesting that offline memory consolidation and retrieval mechanisms underpinned by hippocampal neuronal synchronization are not strongly affected by ethanol. These results indicate that acute ethanol intake mainly affects the encoding of external information but has little impact on internal memory processing.